Application of Compliance Control in Detecting Fraudulent Actions of Participants in the Market of Civil Turnover of Intellectual Property - Zh. A. Kevorkova (Informaciâ i Innovacii)
The article considers compliance control as a new direction of professional activity, as a component of internal control of an economic entity, as a tool for detecting fraudulent activities. The author’s position of application of compliance control at detection of fraudulent actions of intellectual property objects is revealed.